Tambor de crioula: liberdade, cultura e resistência negra no grupo Filhos e amigos de Cururupu – Belém-PA - SILVA, Thamirys Monteiro (2018)
This research had as indoctor The popular manifestation “Tambor de Crioula”. Think about this practice its to make a reference to history,culture, the black manifestation, freedom and joy. Thought the object of research,this project will expose The Black People culture and history, demonstrating the richness of teachings, reflections and feelings. Firstly, this practice its known and common in the State of Maranhao,however in Belem/PA there’s a group of Tambor de Crioula. “Filhos e amigos de Curupu was a dance group created by people that was born in Maranhao, änd then Has been in full activity in the state of Para for more than six years. This research have the object the activity record of this group,as well the refletion about the process of affirmation in the State. Being this question the point of the research: The group/Popular Manifestation Will establish itself in the region. I use a Ethnicity Research to reflect about all aspect cited since Researcher im related to the theme of this profect. To explain the subject I use the author Sergio Ferreti (1979,2010),to reflect about the “Tambor de Crioula”Jorge Sabino (2010) about African Root Antonio Montenegro(1989).I use other author to export about Resistance and Black affirmation as Testimonials of the members of the dance group to further deepen and understand the research.